Activities of daily living among elderly persons with severe aortic stenosis. Issue 3 (30th January 2021) - Fukui, Shogo; Kawakami, Michiyuki; Otaka, Yohei; Ishikawa, Aiko; Yashima, Fumiaki; Hayashida, Kentaro; Muraoka, Kaori; Liu, Meigen
Abstract: Purpose: To determine the level of limitations in activities of daily living (ADL) and instrumental ADL, and identify related factors to instrumental ADL among elderly persons with severe aortic stenosis (AS). Materials and methods: We prospectively enrolled 112 consecutive elderly persons (mean age, 84.6 ± 4.4 y) with severe AS. We assessed ADL and instrumental ADL using the Barthel index (BI) and the Frenchay activities index (FAI), respectively. Cardiac, physical, cognitive and kidney functions, nutritional status, medical histories, and comorbidities were assessed. A multiple logistic analysis was developed to explore related factors to the FAI. Results: The medians (ranges) of BI and FAI were 100 (15–100) and 21 (0–38), respectively. The multiple logistic analysis revealed that a history of heart failure (sβ = −0.189), a history of cerebrovascular disease (sβ = −0.233), the short physical performance battery score ≤ 8 (sβ = −0.272), the mini-mental state examination score ≤ 23 (sβ = -0.168) were significantly related to the FAI ( p < 0.05). Conclusions: Physical frailty, a history of heart failure, cerebrovascular disease, and cognitive decline were independently related to declined instrumental ADL. IMPLICATIONS FOR REHABILIATION: Activities of daily living was well-preserved among elderly persons with severe aortic stenosis. Instrumental activities of daily living varied among patients with aortic stenosis and was sometimes impaired. Physical frailty, a history of heart failure, and a history of cerebrovascular disease were independently associated with instrumental activities of daily living in elderly persons with severe aortic stenosis.